Fear and Greed in Financial Markets: A Clinical Study of Day-Traders - Lo, Andrew W; Repin, Dmitry V; Steenbarger, Brett N (American Economic Review, 2005)
Fear and Greed in Financial Markets: A Clinical Study of Day-Traders by Andrew W. Lo, Dmitry V. Repin and Brett N. Steenbarger. Published in volume 95, issue 2, pages 352-359 of American Economic Review, May 2005